Penguatan Nilai-Nilai Agama dan Moral Anak Usia Dini - Zurqoni, Zurqoni; Musarofah, Musarofah (SYAMIL: Journal of Islamic Education, 2018)
The strengthening of religious and moral values in early childhood is not limited to intellectual aspects, but rather their habituation in daily behavior in school is important. The strengthening of religious and moral values of early childhood requires exemplary people around them, especially teachers. Strengthening religious and moral values in early childhood is done through coaching and learning strategies in a holistic and integrative way to support their optimal growth and development. This study aimed to describe efforts to cultivate the religious and moral values of Early Childhood in Kindergarten ‘Aisyiyah Busthanul Athfal of Samarinda. This research was qualitative by using a phenomenology approach. Sources of data are teachers, student advisers, and students. Data collection technique are participant observation and in-depth interview. While the data analysis technique uses an interactive analysis model of Milles & Huberman, through the process of presenting data, data reduction, and verification/conclusion. The findings showed that the strengthening of religious and moral values of early childhood at Bustanul Athfal Kindergarten in Samarinda were carried out by combining the curriculum of the Ministry of National Education and Al-Islam 'Aisyiyah Bustanul Athfal Early Childhood Education curriculum through program solutions, integrated programs, and programs special. The strengthening strategies of religious and moral values of early childhood at Bustanul Athfal Kindergarten were carried out through the example of the teacher in the school, habituation in behaving according to the child's development. Repetition in attitudes and good behavior is done intensively. The establishment of cooperation between schools and parents and the availability of facilities adequately become supporting factors in the strengthening of religious and moral values of early childhood. While the inhibiting factors include limited infrastructure for the process of overhauling religious and moral values.